2014
DOI: 10.1111/ppe.12106
|View full text |Cite
|
Sign up to set email alerts
|

Early Pregnancy Changes in Bacterial Vaginosis‐Associated Bacteria and Preterm Delivery

Abstract: Background We evaluated the importance of measuring early vaginal levels of eight BV-associated bacteria, at two points in pregnancy, and the risk of spontaneous preterm delivery (SPTD) among pregnant women and the subgroup of pregnant women with a history of preterm delivery (PTD). Methods This prospective cohort study enrolled women at five urban obstetric practices at Temple University Hospital in Philadelphia PA. Women with singleton pregnancies less than 16 weeks gestation self-collected vaginal swabs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
79
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 34 publications
(45 reference statements)
4
79
0
6
Order By: Relevance
“…As outlined above, this observation is also consistent with the fact that BV is a recurrent if not chronic problem for many women. A recent study reported that, among women with a history of PTB, women with high levels of Sneathia species, BVAB1 and Mobiluncus species early in pregnancy, were significantly more likely to experience a spontaneous PTB 94 . We recently reported that the genome of a Sneathia amnii strain from a woman who experienced preterm birth bears various potential pathogenic determinants including cytotoxins and adhesins.…”
Section: Pregnancy and Preterm Birthmentioning
confidence: 98%
“…As outlined above, this observation is also consistent with the fact that BV is a recurrent if not chronic problem for many women. A recent study reported that, among women with a history of PTB, women with high levels of Sneathia species, BVAB1 and Mobiluncus species early in pregnancy, were significantly more likely to experience a spontaneous PTB 94 . We recently reported that the genome of a Sneathia amnii strain from a woman who experienced preterm birth bears various potential pathogenic determinants including cytotoxins and adhesins.…”
Section: Pregnancy and Preterm Birthmentioning
confidence: 98%
“…and Mycoplasma spp. in the vaginal microbiomes of women who deliver preterm [20, 21]. To date there has been no comprehensive study, utilizing high-throughput gene sequencing based methodologies, to characterize the microbiome in the context of preterm premature rupture of the membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of fastidious urogenital bacterial species with quantitative PCR (qPCR) has been associated with preterm birth 15 , persistent BV 16 , and urethritis in men 17 . Here we applied this methodology to investigate the relationship of eight BV-associated bacterial species/genera and three of the most common vaginal lactobacilli with cervicitis in a retrospective case control study of women attending a Seattle STD clinic.…”
Section: Introductionmentioning
confidence: 99%